Habitat filtering influences the phylogenetic structure of avian communities across a coastal gradient in southern Brazil - Gianuca, Andros Tarouco; Dias, Rafael Antunes; Debastiani, Vanderlei Júlio; Duarte, Leandro D. S (Austral ecology, 2014)
The evolution of a particular trait or combination of traits within lineages may affect subsequent evolutionary outcomes, leading closely related species to exhibit higher phenotypic similarity than expected under a simple Brownian‐motion evolutionary model. Niche theory postulates that phenotypes determine species distribution across environmental gradients, leading to a phylogenetic signature in the community assembly. Thus, the incorporation of species phylogeny in the analysis of community ecology structure allows one to link broader environmental, spatial and temporal factors to local, small‐scale ecological processes, thus enabling understanding of community assembly patterns in a broader context. We used the net relatedness index to assess phylogenetic structure within avian communities across a harshness gradient in coastal habitats in southern Brazil. We also evaluated phylogenetic beta diversity, to test whether closely related species exploit habitats with similar environmental conditions. In order to do so, we scaled up phylogenetic information from the species to site level using phylogenetic fuzzy weighting. We found a pattern of phylogenetic clustering in less‐vegetated habitats, namely sandy beach and dunes, which are subject to harsher conditions because of proximity to the ocean. Basal lineages were associated with the more structurally homogeneous sandy beach, while late‐divergence clades occurred in more complex habitats, which were positively related to vegetation cover and height. The observed pattern of phylogenetic clustering suggested the importance of harsh conditions in constraining the distribution of avian lineages. Furthermore, contrasting environmental features between habitats influenced phylogenetic variation, demonstrating the prevalence of phylogenetic habitat filtering. From an applied point of view, such as planning and management of biological reserves, we showed that the full array of habitat patches embedded within coastal ecological gradients must be included in order to preserve distinct evolutionary lineages.